Knowledge and Attitude Regarding Risk Factors of Cardiovascular Diseases among Adolescent Students of a School in Kathmandu Metropolitan City - Sapkota, Asha (Journal of Nursing Education of Nepal, 2022)
Introduction: Cardiovascular diseases (CVDs) are the leading cause of death worldwide. Awareness  and a positive attitude toward risk factors of cardiovascular diseases in adolescence is necessary.  Unable to prevent risk factors among adolescents may result in burden of cardiovascular disease related problems. This study aimed to find out the knowledge and attitude regarding risk factors of  cardiovascular diseases. Methods: A cross sectional research design was used. A total 166 adolescent students of 11th grade  studying in South Western Higher Secondary School were included with the non-probability purposive  sampling technique. The study was carried out during 5th -13th March 2019. Data was collected by a  self-administered structured questionnaire. Descriptive statistics was used for data analysis.  Results: The study showed that the age of the respondents ranged from 16-19 years with a mean age in  years (M = 16.78± SD = 0.80). More than half (57.8%) of the respondents had a fair level of knowledge  on risk factors of CVDs followed by good (22.3%) and poor (19.9%) level of knowledge. Only 34.3%  of the respondents had a positive attitude whereas a nominal number of respondents (12.7%) had a  negative attitude toward risk factors of CVDs.  Conclusion: Knowledge of risk factors of CVDs among adolescents is low. Less than one-third of the adolescents have a positive attitude whereas less than one-fourth have negative attitude toward the risk factors of CVDs. It is necessary to plan and implement awareness programs for raising knowledge,  fostering a positive attitude toward risk factors of CVDs, and forming healthy habits.
Keywords: Adolescent; attitude; cardiovascular diseases risk factors; knowledge